The current state of lesbian, gay, bisexual, and transgender cultural competency among U.S. dermatology residents. Issue 3 (8th July 2022) - Nowaskie, Dustin Z.; Garcia-Dehbozorgi, Sara; Cortez, Jose L.
Abstract : Background: Lesbian, gay, bisexual, and transgender (LGBT) people interface with dermatology providers for many reasons. Implementing culturally competent LGBT dermatologic care necessitates evaluating provider competency to identify where gaps remain. Objectives: To assess the LGBT cultural competency among U.S. dermatology residents. Methods: A self-reporting, cross-sectional survey was emailed to U.S. dermatology program coordinators ( N = 143). LGBT patient exposure, LGBT educational hours, and LGBT cultural competency via the LGBT-Development of Clinical Skills Scale (with the subscales Clinical Preparedness, Attitudinal Awareness, and Basic Knowledge) were measured. Results: Dermatology residents ( N = 119) across the United States completed the survey. They reported caring for less than 20 LGBT patients per year and receiving less than 75 minutes of LGBT education per year. They reported significantly higher Attitudinal Awareness than both Clinical Preparedness and Basic Knowledge; they reported significantly higher Basic Knowledge than Clinical Preparedness. They reported significantly less adequate clinical training and supervision, experience, and competence to assess transgender patients compared to lesbian, gay, and bisexual patients. In general, dermatology residents who reported more LGBT patients and LGBT education also reported higher LGBT cultural competency. Limitations: A larger national sample of U.S. dermatology residents is necessary for generalizability. Conclusions: Currently, there is a lack of LGBT education in U.S. dermatology residency curricula, which may delay addressing the health disparities that exist in this patient population. Due to such dearth of standardized LGBT education, dermatology residents likely do not feel adequately knowledgeable or prepared to address LGBT needs. Both LGBT education and LGBT patient experiences may help alleviate these shortcomings and help LGBT patients feel affirmed in their dermatologic care.